Effects of varying levels of n-6:n-3 fatty acid ratio on plasma fatty acid composition and prostanoid synthesis in pregnant rats - Abdulbari Kassem, Amira; Abu Bakar @ Zakaria, Md Zuki; Goh, Yong Meng; Mohamed Mustapha, Noordin; Ebrahimi, Mahdi (Academic Journals, 2010)
This study investigated the effects of varying dietary levels of n-6:n-3 fatty acid ratio on plasma fatty acid composition and prostanoid synthesis in pregnant rats. Four groups consisting of seven rats per group of non pregnant rats were fed diets with either a very low n-6:n-3 ratio of 50% soybean oil (SBO): 50% cod liver oil (CLO) 1:1 group , a low ratio of 84% SBO: 16% CLO 6:1 group, a high ratio of 96% SBO: 4% CLO 30:1 group and control group was given only rat chow diet. Blood samples were taken at day 15 post mating and the plasma was analyzed for fatty acid profile, specifically the n-6:n-3 fatty acid ratio and prostaglandins F2α and E2. The n-3 polyunsaturated fatty acids (PUFA) in plasma of group 1:1 were significantly (P < 0.05) higher than the other groups, while the n-6:n-3 fatty acid ratio was significantly lower. The total n-6 PUFA was significantly higher (P < 0.05) in group 30:1 as compared to the control and 1:1 groups. The total PGF2α and PGE2 were significantly higher (P < 0.05) in group 30:1 rats fed a diet high in n-6 or n-6:n-3 fatty acids. The diet higher in n-6 fatty acids appear to increase arachidonic acid( AA) and prostaglandins synthesis in plasma of rats. PGE2 productions in plasma were significantly lower in rats fed diets with a lower dietary ratio of n-6:n-3 fatty acids than in those fed diets with a higher dietary ratio. Regression analysis revealed a significant positive correlation between PGF2α and PGE2 and the ratio of n-6:n-3, and significant positive correlation between different ratio n-6:n-3 on fatty acid plasma compstion and PGF2α and PGE2 concentration on plasma. These results demonstrated that the dietary ratio of n-6:n-3 modulates PGF2α and PGE2 production. The n-6:n-3 fatty acid ratio significantly affected plasma fatty acids profile and prostaglandin synthesis in pregnant rat.